Examining the Impact of Mathematical Critical Thinking Skills on Matrix Learning Outcomes - Majid Majid; Fahri Katuri; Kartin Usman; Syafrudin Katili (AL-ISHLAH: Jurnal Pendidikan, 2025)
Student learning outcomes represent their understanding of subject material and serve as a benchmark for evaluating educational effectiveness. A preliminary investigation at SMA Negeri 7 Gorontalo revealed low student performance in matrix-related mathematics topics. Among various factors influencing learning success, critical thinking stands out as a key internal factor in mathematics education. This study employed a quantitative, descriptive-correlational design with an ex post facto approach. It aimed to assess the mathematical critical thinking skills of Grade XI students and to examine their relationship with learning outcomes on matrix material. Critical thinking was evaluated using four indicators: analyzing, evaluating, explaining, and concluding. Findings indicated that most students had not yet achieved an optimal level of mathematical critical thinking, with an average score of 56.34 across a sample of 50 students. Correlational analysis revealed a significant positive relationship between critical thinking skills and learning outcomes, with critical thinking accounting for 61.62% of the variance in performance. The data suggest that mathematical critical thinking skills play a substantial role in determining student success in matrix material. Given the strong correlation observed, enhancing these skills may lead to measurable improvements in learning outcomes. There is a significant and positive relationship between students' mathematical critical thinking skills and their learning outcomes in matrix material. Efforts to strengthen critical thinking could be an effective strategy to improve academic performance in mathematics.